A Gauss type functional equation - Silvia Toader; Themistocles M. Rassias; Gheorghe Toader (International Journal of Mathematics and Mathematical Sciences)
Gauss' functional equation (used in the study of the arithmetic-geometric mean) is generalized by replacing the arithmetic mean and the geometric mean by two arbitrary means.